2020
DOI: 10.2337/db19-0701
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Adipokine Gremlin 1 Antagonizes Insulin Action and Is Increased in Type 2 Diabetes and NAFLD/NASH

Abstract: The BMP2/4 antagonist and novel adipokine Gremlin 1 is highly expressed in human adipose cells and increased in hypertrophic obesity. As a secreted antagonist, it inhibits the effect of BMP2/4 on adipose precursor cell commitment/differentiation. We examined mRNA levels of Gremlin 1 in key target tissues for insulin and also measured tissue and serum levels in several carefully phenotyped human cohorts. Gremlin 1 expression was high in adipose tissue, higher in visceral than in subcutaneous tissue, increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 29 publications
4
61
1
1
Order By: Relevance
“…Adiponectin and leptin can independently predict the onset of NAFLD that is why they may be taken into consideration as potential predictive biomarkers for NAFLD [ 94 ]. Recently, researchers found that novel adipokine Gremlin 1 can antagonize insulin signaling, is positively correlated with the percentage of body fat and IR in T2DM and NAFLD/NASH subjects, and also could represent a potential biomarker or therapeutic target [ 95 ].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Adiponectin and leptin can independently predict the onset of NAFLD that is why they may be taken into consideration as potential predictive biomarkers for NAFLD [ 94 ]. Recently, researchers found that novel adipokine Gremlin 1 can antagonize insulin signaling, is positively correlated with the percentage of body fat and IR in T2DM and NAFLD/NASH subjects, and also could represent a potential biomarker or therapeutic target [ 95 ].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…201 The novel adipokine gremlin 1 antagonizes insulin action and is increased in type 2 diabetes and NAFLD/NASH. 202 Diet and nutrient intake. Inadequate vitamin and fiber content in the diet, as well as simple carbohydrates, saturated fat, and excessive cholesterol, are associated with NASH development.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…A subcutaneous abdominal adipose tissue biopsy was performed. The biopsies (approximately 20-30 mg) were obtained with a needle aspiration technique, from the paraumbilical region after local infiltrative anesthesia with lidocaine (20 ml, 0.5%) 28 .…”
Section: Study Populationmentioning
confidence: 99%